A preliminary geometric morphometrics assessment of two forensically important blow fly larvae in Malaysia, Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) - Sharanya B.; Raja Muhammad Zuha Raja Kamal Bashah (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
In forensic entomology, the age of blow fly larvae (Diptera: Calliphoridae) that feed on decomposing human tissues can be used as reference in minimum post mortem interval (mPMI) estimation. To establish mPMI based on larval age, it is important to correctly identify larva species based on their morphological characteristics as larval developments from where they were collected are species-specific. Recently, landmark-based geometric morphometric analysis has been found useful to discriminate species and provide visual shape variations. The objective of this study was to assess the utilization of this technique on two forensically important blow fly species in Malaysia, i.e. the Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) based on the cephalopharyngeal skeletons of the larvae. A total of 10 landmarks on cephalopharyngeal skeleton were established and analyzed with geometric morphometric functions in MorphoJ™ software. Cephalopharyngeal skeleton centroid size, which represented the individual cephalopharyngeal skeleton shape profile, were statistically different between C. megacephala and C. rufifacies (p<0.001). Based on the landmark plot shifts, the two species could be differentiated based of parastomal bar, the clipeal arc, apical hook, upper margin of ventral cornu and lower margin of ventral cornu. These differences were well defined in visual presentation by using principal component analysis with 100% cross validation reassignment percentage. However, large scale study should be considered for a more complete cephalopharyngeal skeleton shapes profiles of forensically important Calliphoridae.